Penguatan Tata Kelola Desa Berbasis Nilai Lokal Madene dan Inovasi Digital di Desa Busalangga Barat - Manuain, Alfandy Florian; Fanggidae, Ivan Gideon; Pandie, Ardy Yosafat; Benyamin, Rouwland Alberto; Long, Belandina Liliana; Tamba, Dumanita; Seger, Marini Sari Dewi; Kohlikin, Rafi Akhsanul (Universitas Dinamika, 2025)
Strengthening village governance through local wisdom and simple digital technology is a strategic approach to addressing participation and transparency challenges. This community engagement program was implemented in Busalangga Barat Village, Rote Ndao Regency, aiming to revitalize the local value of madene and introduce a Microsoft Excel VBA-based village administration information system. The program utilized community education, technology simulation, advocacy, mediation, and consultation methods, structured into four stages: problem identification, material development, core implementation, and remote monitoring and evaluation. The program began with a Focus Group Discussion (FGD) involving traditional leaders, village officials, youth, and women's groups. The discussion generated a shared awareness that madene—as a cultural expression of mutual cooperation—remains relevant in restoring participatory governance and village deliberation practices. The system training enabled village officials to manage population data and generate administrative documents automatically. The application also integrates real-time population updates, such as changes following birth, death, or migration events. This activity demonstrates that cross-regional collaboration combining local values with appropriate digital technology can drive social transformation and improve public service delivery at the village level. This model is adaptable and replicable in other rural contexts with appropriate adjustments.